2008
DOI: 10.1097/tp.0b013e3181910f51
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Intestinal Retransplantation: Techniques, Management, and Outcomes

Abstract: Improved long-term survival and outcome in pediatric Re-ITx may be attributed to improvements in initial immunosuppression protocols, technical modifications, proper timing, and improved infectious disease monitoring. Careful patient selection and posttransplant management are essential for successful long-term outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
1
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 19 publications
1
25
1
1
Order By: Relevance
“…This result was similar to those from the singlecenter series reported by Mazariegos et al (10). In this report, immunosuppression before the retransplant, the timing of the enterectomy, and a period of hyperalimentation after the retransplant were all considered important for outcome (10). In our analysis, for adults mainly, rejection was the major cause of graft failure.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This result was similar to those from the singlecenter series reported by Mazariegos et al (10). In this report, immunosuppression before the retransplant, the timing of the enterectomy, and a period of hyperalimentation after the retransplant were all considered important for outcome (10). In our analysis, for adults mainly, rejection was the major cause of graft failure.…”
Section: Discussionsupporting
confidence: 91%
“…More recent single-center data have shown better results (10). Magee et al (3) reported liver, kidney, heart, and lung retransplant outcomes during the most recent decade in the United States; however, they did not address ITx retransplants.…”
mentioning
confidence: 95%
“…Improved long-term survival and outcomes in pediatric intestinal transplantation has been observed both in primary and in retransplantations [33]. The increased success has been attributed to many clinical and technical modifications, including posttransplantation immune monitoring.…”
Section: Preformed and De Novo Dsa Associated With Early Acr In Multimentioning
confidence: 99%
“…There were 18 patients who received a retransplantation also contributed in primary transplants (n = 200). However, the data were analyzed based on events (not on patients) as observational units, as previously done by us and other groups . The data were summarized using means with standard deviations, or medians with interquartile ranges for continuous variables, and percentages for discrete variables.…”
Section: Methodsmentioning
confidence: 99%